2007
DOI: 10.1017/s0022029907002543
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic survey ofLactococcus lactisstrains to six antibiotics by Etest, and establishment of new susceptibility-resistance cut-off values

Abstract: In order to establish cut-off values for Lactococcus lactis to six antibiotics to distinguish susceptible and intrinsically resistant strains from those having acquired resistances, the minimum inhibitory concentration (MIC) of tetracycline, erythromycin, clindamycin, streptomycin, chloramphenicol and vancomycin was determined in 93 different Lc. lactis strains using the Etest. These bacterial strains were originally isolated from dairy and animal sources in widely separated geographical locations. Cut-offs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…Our results revealed a high incidence (40 %) of L. lactis strains showing acquired (multi)resistance to tetracycline, streptomycin, kanamycin clindamycin, vancomycin and gentamicin. The resistance to tetracycline has been previously found in L. lactis from bovine milk and derived products, and it has been associated with the common use of this antibiotic for the treatment of bovine infections [20,41]. The phenotypic resistance to clindamycin was previously described in three strains of L. lactis isolated from raw milk [40].…”
Section: Discussionmentioning
confidence: 97%
“…Our results revealed a high incidence (40 %) of L. lactis strains showing acquired (multi)resistance to tetracycline, streptomycin, kanamycin clindamycin, vancomycin and gentamicin. The resistance to tetracycline has been previously found in L. lactis from bovine milk and derived products, and it has been associated with the common use of this antibiotic for the treatment of bovine infections [20,41]. The phenotypic resistance to clindamycin was previously described in three strains of L. lactis isolated from raw milk [40].…”
Section: Discussionmentioning
confidence: 97%
“…The MIC for streptomycin for the L. lactis Bu2-60 recipient strain and its transconjugants was 1,024 g/ml. Both recipient types, lactococcal and enterococcal, were susceptible to tetracycline, and the MIC was Ͻ1 g/ml (18). In vivo conjugation experiments in germfree rats.…”
Section: Vol 75 2009 Transfer Of Tn916-like Elements From L Lactismentioning
confidence: 99%
“…Nevertheless, many investigators have recently speculated that commensal bacteria, including lactic acid bacteria (LAB), may act as reservoirs of antibiotic resistance determinants (40). Genes conferring acquired resistance to tetracycline, erythromycin, and vancomycin have been detected and characterized for Lactococcus, Enterococcus, and Lactobacillus species isolated from fermented meat and milk products (13,18,23,49,50,56). Introduction of such bacteria into humans through ingestion of commercial food products may have negative consequences by dissemination of antibiotic resistance genes via the food chain to the resident microbiota of the human gastrointestinal tract and, in the worst case, to pathogenic bacteria (4,17,55).…”
mentioning
confidence: 99%
“…This method is particularly useful in the study of the efect of probiotics, which are often required to identify probiotic bacteria of the commensal microlora [17]. Recently it was reported that the simultaneous use of ATB and supportive probiotic therapy, which can help to restore intestinal microbiota, can also expand the antibiotic resistance of bacterial intestinal bacteria [18,19].…”
Section: Testing Of Atb Efect On Animalsmentioning
confidence: 99%